New physics and signal-background interference in associated pp → Hz production - Englert, Christoph; Rosenfeld, Rogerio [UNESP]; Spannowsky, Michael; Tonero, Alberto [UNESP] (IOP Publishing, 2016)
We re-investigate electroweak signal-background interference in associated Higgs production via gluon fusion in the presence of new physics in the top Higgs sector. Considering the full final state pp → bb+ℓ- (ℓ = e, μ), we discuss how new physics in the top Higgs sector that enhances the ZZ component can leave footprints in the HZ limit setting. In passing we investigate the phenomenology of a class of new physics interactions that can be genuinely studied in this process.